2018
DOI: 10.1097/ico.0000000000001532
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Irregular Astigmatism and Curvature Changes After Small Incision Lenticule Extraction: Three-Year Follow-Up

Abstract: Three years after SMILE, there was a reduction of posterior astigmatism in high refractive corrections. This could result in undercorrection in high refractive treatments. Total irregularities increased despite the compensatory effect of the posterior corneal surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…With respect to corneal stability, we observed significant changes in MCFC from 3 months to 4 years post-SMILE, in line with prior findings (25,26). We additionally observed no changes in the posterior corneal surface following SMILE.…”
Section: Discussionsupporting
confidence: 91%
“…With respect to corneal stability, we observed significant changes in MCFC from 3 months to 4 years post-SMILE, in line with prior findings (25,26). We additionally observed no changes in the posterior corneal surface following SMILE.…”
Section: Discussionsupporting
confidence: 91%
“…This has been reported in a recent study by Sideroudi et al. 53 It has also been supported by the results presented by Ganesh et al. 54 …”
Section: Discussionsupporting
confidence: 87%
“…Moreover, they induce different postoperative biomechanical responses, which may result in different remodeling of the anterior and posterior cornea. [1][2][3][4][5][6][7][8][9][10][11][12] Several in vivo and ex vivo studies as well as mathematical models have shown that LASIK may cause a greater reduction in the biomechanical strength of the cornea compared with SMILE, which is mainly associated with the flap creation in LASIK. A better preservation of the corneal tensile strength may result in a more stable corneal morphology and possibly a more stable refractive outcome in the long term.…”
mentioning
confidence: 99%